Avaliação da qualidade de vida do estudante surdo do Centro de Capacitação dos Profissionais da Educação e Atendimento às Pessoas com Surdez (CAS) de Goiânia - Galvão, Marcus Vinicius Alves (2017)
Introduction: Deaf people and deafness have been the focus of study for different areas of knowledge such as education, law and health. These were organized to try to explain the different dimensions of the subject and contributed in different ways to the visibility of the subject. Objective: To evaluate the quality of life of the deaf schoolchild. Methods: A cross-sectional study was carried out on 29 deaf students between 13 and 26 years of age attending the Specialized Educational Assistance at the Center for the Training of Professionals of Education and Assistance to Persons with Deafness in the first semester of 2016, using the WHOQOL-Bref e Dis in Pounds. The data collected were analyzed using the Statistical Package for the Social Sciences (SPSS), version 23 for Windows. For the description of the QoL, we used averages, medians and standard deviations in Raw scale. In addition, the T-Student test and the Kolmogorov-Smirnov test were used to compare the variables. Results: 57% reported incomplete secondary education. 82% live in Goiânia; in comparison with satisfaction with their own health, 86.2% were satisfied with their own health; the sociodemographic data and quality of life (QoL) in the WHOQOL-Bref in Pounds, the age group in the physical and social domains and the schooling in the environmental domain were significant. As for the WHOQOL-Dis domains in Libras, the statistical correlation was shown to be statistically significant in the social and environmental domains. Conclusion: In the common sense when evaluating subjects with some deficiency, we expect negative results. But contrary to this opinion, the deaf students of this research showed a good quality of life and good perception.